PERLINDUNGAN ANAK PIDANA DI LEMBAGA PEMBINAAN KHUSUS ANAK DALAM PERSPEKTIF MODEL PEMBINAAN ANAK SECARA PERORANGAN - Irma Cahyaningtyas (Faculty of Law, University of Muhammadiyah Malang, 2016)
A child who didn’t get affection they tend to be juvenile and consequence may be able to carry out deviate action which collide with regulation. These child must execute criminal process that will ended to a behavior treatment that will take place in The Juvenile Correction. One of the treatment that exist in The Juvenile Correction is the treatment that actually based to child. Those kind of treatment called the individual treatment model. This paper background by issues, firstly how individual treatment model implementation in The Juvenile Correction; second what kind of constraints which found in the individual treatment model in The Juvenile Correction. Research methods used were 1) juridical empirical method;2) socio legal approach;3)case study in The Juvenile Correction in Kutoarjo. Analysis concerning are explained, first individual treatment model was already known. There were the type of individual treatment model were both religiousness and counseling treatment. But, for implementation that model could not implement properly.